Drug Resistance-Associated Mutations in ERG11 of Multidrug-Resistant Candida auris in a Tertiary Care Hospital of Eastern Saudi Arabia - Reem AlJindan; Doaa M. AlEraky; Nehal Mahmoud; Baha Abdalhamid; Mashael Almustafa; Sayed AbdulAzeez; J. Francis Borgio (Journal of Fungi, 2020)
Candida auris is an emerging multi-drug resistant pathogen with high mortality rate; nosocomial infections have been reported worldwide, causing a major challenge for clinicians and microbiological laboratories. The study aims to describe new cases of C. auris and detect drug resistance-associated mutations of C. auris by the sequencing of ERG11 and FKS1 genes. A total of six specimens were collected from blood, urine, ear swab, and groin screening samples. Isolates were incubated for 48 h on Sabouraud Dextrose agar (SDA) at 42 °C, then confirmed by MALDI-TOF MS. Furthermore, antifungal susceptibility testing was performed using the Vitek 2 system to detect Minimum Inhibitory Concentrations (MICs) of six antifungals. Sequences of 18S rRNA gene and ITS regions from isolates and phylogenetic analysis were performed. Gene sequencing was analysed to detect drug resistance-associated mutations by FKS1 and ERG11 genes sequencing. All C. auris isolates were confirmed by MALDI-TOF MS, and evolutionary analyses using sequences of 18S rRNA gene and ITS region. Antifungal susceptibility testing showed that all isolates were resistant to fluconazole. Sequencing of ERG11 and FKS1 genes from the isolates revealed the presence of two (F132Y and K143R) drug resistance-associated mutations in ERG11, however, FKS1 gene was devoid of mutations. The study sheds light on a public health threat of an emerging pathogen, and the hospital implemented strict contact screening and infection control precautions to prevent C. auris infection. Finally, there is a critical need to monitor the antifungal resistance in different geographical areas and implementation of efficient guidelines for treatment.